Community-Based Waste Cooking Oil (WCO) Soap-Making for Environmental Awareness and Economic Stability in Labis, Johor - RENU YASHWINI BASKARAN; Ali, Roslinda; Mashori, Sumaiya (Progress in Engineering Application and Technology, 2026)
The improper disposal of waste cooking oil (WCO) poses not only environmental and health risks but also represents an untapped economic potential. This study examined community awareness and readiness to adopt sustainable practice in Labis, Johor, through a hands-on demonstration of soap making using WCO. A questionnaire survey involving 73 respondents was conducted across pre-implementation, implementation, and post-implementation phases. Data were analyzed using descriptive statistics, reliability analysis, and the Mann–Whitney U test. The findings revealed a moderate-to-high level of awareness regarding the risks associated with WCO. The hands-on soap-making demonstrations proved to be more effective than awareness initiatives alone in influencing behavioral change. Strong participation was observed among women, students, and older individuals, many of whom expressed an interest in continuing soap making for personal use or income generation. Employment and student status significantly influenced awareness levels, whereas gender did not have a significant effect. In conclusion, community-based soap-making from waste cooking oil (WCO) demonstrates strong potential in enhancing environmental sustainability and promoting local economic empowerment, as reflected through positive participant feedback, increased awareness, and active community engagement observed during the programme.